Rectum-spacer related acute toxicity – endoscopy results of 403 prostate cancer patients after implantation of gel or balloon spacers - Andreas Schörghofer; Martin Drerup; Thomas Kunit; Lukas Lusuardi; Josef Holzinger; Josef Karner; Michael Groher; Christoph Zoubek; Rosemarie Forstner; Felix Sedlmayer; Frank Wolf (Radiation Oncology, 2019)
Abstract Background Rectal spacers are used to limit dose to the anterior rectal wall in high dose external beam radiation therapy of the prostate and have been shown to reduce radiation induced toxicity. Here we report the complication rate and toxicity of the implantation procedure in a large cohort of patients who have either received a gel- or balloon-type spacer. Methods In total, 403 patients received rectal spacing, 264 with balloon, 139 with gel. Allocation was non-randomized. Two hundred seventy-six patients were treated with normofractionated regimen, the remaining 125 patients in moderate hypofractionation. Spacer related acute and late rectal toxicity was prospectively assessed by endoscopy using a mucosa scoring system (Vienna Rectoscopy Score) as well as CTCAE V.4. For the balloon subgroup, position and rotation of balloon spacers were additionally correlated to incidence and grade of rectal reactions in a post-hoc analysis of post-implant planning MRIs. Results Overall rectal toxicity was very low with average VRS scores of 0.06 at the day after implantation, 0.10 at the end of RT, 0.31 at 6 months and 0.42 at 12 months follow up. Acute Grade 3 toxicity (rectum perforation and urethral damage) directly related to the implantation procedure occurred in 1.49% (n = 6) and was seen exclusively in patients who had received the spacer balloon. Analysis of post implant MR imaging did not identify abnormal or mal-rotated positions of this spacer to be a predictive factors for the occurrence of spacer related G3 toxicities. Conclusions Spacer technology is an effective means to minimize dose to the anterior rectal wall. However, the benefits in terms of dose sparing need to be weighed against the low, but possible risks of complications such as rectum perforation.